Efektivitas Media Gambar Berseri terhadap Keterampilan Menulis dan Membaca pada Muatan Bahasa Indonesia Siswa Kelas II SDI Detuduli - Yustina Serliana Mbasi; Frederiksen N.S. Timba; Maria Herliyani Dua Bunga (Departement of Mathematics Education, 2023)
This study aims to determine the application of serial picture media to the reading and writing skills of Indonesian language content for class II students at SDI Detduli. This research was conducted at SDI Detuduli using quantitative research methods. The population of this research is SDI Detuduli and the sample in this research is class II students (8 people). Research data collection instruments in the form of pre test and post test. The results showed that there was an effect of applying serial picture media to the Indonesian language skills of class II students at SDI Detduli. From the results of the study it can be concluded that the application of serial image media at SDI Detuduli succeeded in increasing student skills, with various teacher skills in teaching and creativity in the application of media.